Implementasi Kurikulum Merdeka (IKM) di Sekolah Dasar dalam Mengembangkan Profil Pelajar Pancasila - Angga; Asep Herry Hernawan; Tita Mulyati (Jurnal Elementaria Edukasia, 2023)
The application of the Pancasila student profile can strengthen character and competency development, train problem-solving skills, and be responsible and concerned about issues around. This study aims to describe the implementation of the independent curriculum in developing the profile of Pancasila students in elementary schools. The research method used is the study of literature. Data collection with the keywords "independent curriculum" and "Pancasila student profile" through books and journals or articles from google scholar. The stages of research are carried out through: (1) reviewing the formulation of questions; (2) conduct literature reviews; (3) filter and select relevant literature; (4) analyze and synthesize the content of the appropriate literature; (5) control the quality of writing journal articles according to predetermined topics; and (6) present the results of the literature review. The results showed that IKM began to be implemented by elementary schools that were selected to become Driving Schools with the mandatory option of Mandiri Berbagi. The Merdeka Curriculum is devoted to developing the Pancasila Student Profile through intracurricular, co-curricular, extracurricular, and positive cultural activities in elementary schools. Elementary schools that have not yet become Driving Schools are given the option to implement the Independent Curriculum in accordance with school conditions. SMIs at the primary school level have so far been organized quite well and will be improved in the following year. So, this IKM will be implemented thoroughly in elementary schools in 2024.